An interaction model and infrastructure for localized activities in pervasive computing environments - Pinto, Helder (2007)
This paper presents an interaction model for pervasive computing environments supporting localized activities, i.e., activities strongly associated to a specific physical environment. We are particularly interested in activities performed by occasional visitors to public spaces. This interaction model is characterized by an activity-centered approach to pervasive computing and is defined in a conceptual model inspired by Activity Theory. ActivitySpot, a software infrastructure implementing this conceptual model, is also presented. User interaction in ActivitySpot is based on simple, everyday pervasive computing devices, which facilitates usage learning and allows for a wide user population. ActivitySpot has supported the deployment of several pervasive computing solutions for localized activities. Our conceptual model has been evaluated by user studies run at different public spaces and global results demonstrate the model’s suitability to the targeted type of scenario.